Strategies of Professional Nursing Autonomy - Mostafa Roshanzadeh; Mirhossein Aghaei; Ehsan Kashani; Zahra Pasaeimehr; Ali Tajabadi (Kurdistan University of Medical Sciences, 2018)
Strategies such as expansion of roles, development of associations, documentation, determining proper measurement tools, specific and accurate definitions, interprofessional team formation, having the support of administrators, expansion of nursing services in the community, and interprofessional educations can play an effective and important role in the professional autonomy of nurses. According to Papathanassoglou et al., one of the important strategies of developing professional autonomy is expansion of the professional roles of nurses (1). In order to achieve positive professional identity and development of autonomy, nurses need to improve their public image and gain a stronger position in healthcare organizations, which can be obtained through increasing their presence in scientific and professional assemblies and specialized nursing organizations. In general, specialized nursing organizations must use strategies and establish rules to strengthen their professional identity and achieve autonomy in nurses. Nursing standards act as a measure taken to form the professional and legal basis for nursing and obtain safe performance (2). The existence of standards makes nurses accountable and responsible for their actions and provides the necessary knowledge, attitude, skills, and judgment for clinical decision-makings. Nursing profession rules must be accurately employed by management groups as a factor for professional autonomy along with official relations. Having a determined function area by individuals and maintaining professional autonomy could be achieved by observing the professional regulations and establishing a job description. In this respect, one of the effective strategies is the use of hospital information system and quality of data report documentation, which can play an important role in achieving professional development. While the nursing process is carried out by nurses, it is necessary to improve the documentation system to further enhance the accreditation of interventions and increase its quality to achieve high-quality interprofessional communications. According to Toulabi et al., nursing documentation system could be improved by providing a prepared nursing report form, placing the network on a portable electronic device or above the patients’ bedside, and having access to remote health, which consequently contribute to effective implementation of data recording system. Improvement of capabilities of the nursing electronic documentation system and interprofessional relations will lead to the provision of accurate and scientific care. In addition, enhancement of nursing documentation system leads to the recognition of duties and responsibilities by nurses and determining of the position of the field for other healthcare groups (3). Moreover, nursing information documentation systems increase the improvement of care and functional areas of nurses in fields of management and education, thereby improving the decision-making of nurses and their role as a member of the interprofessional team. One of the important challenges in the field of professional autonomy is the vague definition and the use of inappropriate means for measurement. The existence of tools plays an important role in assessing and determining the strengths and weaknesses of roles and responsibilities of nurses. According to Skar, the lack of a clear definition of autonomy has led to multiple interpretations and the creation of a one-dimensional view on independent performance of nurses. Therefore, a definite definition of autonomy and a certain theory are required in the field of nursing (4). Another important issue to be considered in this area is teamwork, which is a necessity of cooperation of nurses with other team members. According to Sollami et al., effective teamwork increases the quality of care and motivation and decreases work conflicts. One of the important influences of teamwork is increasing professional autonomy, which itself leads to improved skills, competency, responding ability, trust, respect, and decision-making ability in nurses (5). Independent decision-making requires the approval and support of managers since it improves the self-confidence, efficiency and progress of work, motivation and safety. Studies in this field have suggested that managers in clinical systems can help the autonomy of nurses by making proper decisions. According to Sarkoohijabalbarezi et al., inefficient management structures are the most important deficiencies in achieving progress in the nursing profession, creating negative attitudes (e.g., frustration and dissatisfaction) in nurses toward their profession and, thereby, causing the intention to leave the profession (6). The support of managers and the approach used by these individuals to resolve conflicts among their staff can be effective in promoting relationships between members of a healthcare team. In fact, managers can contribute to the improvement of the interprofessional communications between employees with the appropriate support of the personnel. The development of nursing services at the community level is a great opportunity for nurses in the field of employment and presenting nursing society's capabilities in promoting community health and providing qualitative and suitable services to the public. In addition, expanding the primary services with the management of nurses in the community determines how a university nurse can provide people with low and affordable services. In this regard, Gagne and Choi have marked that service provision systems at the community level can play a significantly important role in the decision-making and planning, prevention, care, and referral to the physician in the healthcare team with the leadership of the nurses. Furthermore, promoting primary care by nurses will create an opportunity for introducing the nursing community to the people. Management and planning of these services by nurses at an extensive level in the community increase the professional autonomy of these individuals (7). Freedom of action and authority in managing the conditions of community members and providing and improving care can be effective in the autonomy of nurses. On the other hand, while nurses can provide people with the most complex issues and problems and most critical services at home, cultural problems in society and obstacles to these activities must be resolved. Finally, it seems that special attention must be paid to interprofessional education in order to achieve professional autonomy. In this respect, the priorities of nursing education must focus on creating educational programs that increase the strength of individuals. Therefore, it seems crucial to correct the curriculum of students to better recognize and respect themselves and develop their independent behaviors, and use educational strategies and proper interactive styles for empowering students and acquiring professional autonomy.